Probing cytochrome P450 bioactivation and fluorescent properties with morpholinyl-tethered anthraquinones. Issue 8 (1st May 2018) - Errington, Rachel J.; Sadiq, Maria; Cosentino, Laura; Wiltshire, Marie; Sadiq, Omair; Sini, Marcella; Lizano, Enric; Pujol, Maria D.; Morais, Goreti R.; Pors, Klaus
Graphical abstract: Abstract: Structural features from the anticancer prodrug nemorubicin (MMDX) and the DNA-binding molecule DRAQ5™ were used to prepare anthraquinone-based compounds, which were assessed for their potential to interrogate cytochrome P450 (CYP) functional activity and localisation. 1, 4-disubstituted anthraquinone8 was shown to be 5-fold more potent in EJ138 bladder cancer cells after CYP1A2 bioactivation. In contrast, 1, 5- bis ((2-morpholinoethyl)amino) substituted anthraquinone10 was not CYP-bioactivated but was shown to be fluorescent and subsequently photo-activated by a light pulse (at a bandwidth 532–587 nm), resulting in punctuated foci accumulation in the cytoplasm. It also showed low toxicity in human osteosarcoma cells. These combined properties provide an interesting prospective approach for opto-tagging single or a sub-population of cells and seeking their location without the need for continuous monitoring.